Creating Non-Linear Interactive Narratives with Fábulas Model - Pinto, Hedvan Fernandes; Busson, Antonio José Grandson; Soares Neto, Carlos de Salles; Vale, Samyr Beliche (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Interactive narratives are multimedia applications that makes use of digital resources in order to enrich the reading experience. These applications are more complex to produce than digital books because they require the specification of spatial and temporal synchronization among medias. They can also define non-linear stories in contrast to linear books. The authoring of interactive narratives establishes an application domain that is defined by a set of functional and non-functional requirements. This paper presents F´abulas, a multimedia conceptual model created for the declarative development of non-linear interactive narratives. F´abulas model is small and designed for content producers like teachers, parents or writers. This paper illustrates the expressiveness and applicability of this model by describing a sample application that shows some of the F´abulas features.